Improving Indonesian Language Learning Outcomes Through a Jigsaw Type Cooperative Approach for Junior High School Students - Firman Firman; Mirnawati Mirnawati; Fadly Akbar; Sakinah Fitri (P3I Luwu Raya, 2020)
This study aims to improve economic learning outcomes through a Jigsaw type cooperative approach in grade VII junior high school students. The results of this classroom action research are expected to provide significant benefits, both for individuals and for educational institutions. The results of the implementation of the first cycle showed that there were 22 (55%) students in very low category, 4 (10%) students in low category, 10 (25%) students in medium, 4 (10%) high students, and there are no students in the very high category. If the average score of economic learning outcomes is entered into five categories, then the mastery category is 0-39% (low). While the results of the implementation of the second cycle showed progress that and 40 students, only 4 students (10%) had very low mastery levels, 8 students (20%) had low mastery levels, 14 students (35%) had moderate mastery levels, 9 students (22.5%) with a high level of mastery, 5 students (12.5%) with a very high level of mastery. If the average score of economic learning outcomes is put into five categories, then the mastery level is 55-74% (medium). There were 29 students (72%) who had very low mastery of economics learning outcomes in the first cycle, the second cycle was reduced to 3 students (7.5%). In the first cycle there was only 1 student (2.5%) who had a high level of mastery and in the second cycle it changed to 8 students (20%) who had a high level of mastery. In the first cycle there were no students in the very high category, however, in the second cycle there were 4 students (10%) who had a high level of mastery.